The Predicaments Encountered by International Class Program Students of English Medium Instruction Class in Higher Education at Universitas Negeri Makassar - Wahdaniah Wahdaniah; Ahmad Talib; Ulil Amri (Journal of Excellence in English Language Education, 2023)
This study aims to find out the predicaments encountered by the international class program students of English Medium Instruction (EMI) class. The participants of this study were ten International Class Program students in the sixth semester of the Biology Education study program of the Faculty of Mathematics and Natural Sciences at Universitas Negeri Makassar. The method of this study was a descriptive qualitative design, and the interview was the instrument for collecting data. The result showed that the predicaments encountered by the students of the EMI class in the Biology Education study program ICP of the Faculty of Mathematics and Natural Sciences at Universitas Negeri Makassar were: 1) Present the material by the lecturers: a) limited knowledge of vocabulary, b) unfamiliar accent in lecturer’s pronunciation, c) low listening skill; 2) Understanding the textbooks: a) limited knowledge of vocabulary, and b) no division of students’ level of ability. 3) Understanding the scientific journal to write practicum reports: limited knowledge of vocabulary. 4) Writing a practicum report: difficulty with grammar. 5) Speaking in the class of presentation: a) difficulty in pronunciation, and b) limited knowledge of vocabulary.